Netralitas Aparatur Sipil Negara dalam Penyelenggaraan Pemilu - Nizza Kartika Sari; Adelia Trisna Juniar (CV Era Digital Nusantara, 2024)
This research aims to analyze law enforcement related to ASN Neutrality in elections based on laws and regulations. ASN neutrality is an important principle in ensuring the integrity and fairness of the democratic process. This research uses a normative juridical method with a statutory approach to analyze the legal framework governing ASN neutrality in the context of elections. Primary, secondary, and tertiary legal materials are used to support this analysis, including Law No. 5 of 2014, Law No. 7 of 2017, and other relevant regulations. Existing regulations provide a strong foundation for maintaining ASN neutrality. However, implementation still faces challenges, including political pressure and lack of understanding of the importance of neutrality. Strengthening supervision by relevant institutions is needed to improve ASN compliance with neutrality rules. ASN's partiality in elections can lead to public distrust of government institutions. In the context of Indonesia's plural society, political diversity is a necessity. Therefore, the neutrality of ASN is fundamental to ensure that there is no discrimination or political pressure against certain groups of people so as to maintain social stability and community cohesion. By strengthening the implementation of regulations, improving supervision, and increasing ASN awareness, it is expected to create a competitive and transparent political environment, support the sustainable development of democracy in Indonesia, and increase ASN awareness of their roles and responsibilities in Indonesia's democratic process.